Non-conventional Management of Plant-Parasitic Nematodes in Musaceas Crops - Riascos Ortiz, Donald; Mosquera Espinosa, Ana T.; Varón de Agudelo, Francia; Gonçalves Oliveira, Claudio Marcelo; Muñoz Flórez, Jaime Eduardo (Springer Nature, 2025)
The production of Musa AAB Simmonds (plantain) and M. acuminata AAA (banana) is threatened by different plant-parasitic nematodes (PPN) worldwide. Main PPN such as Radopholus similis, Meloidogyne spp., Pratylenchus spp., Rotylenchulus reniformis, and Helicotylenchus spp. may cause yield losses up to 80%. Most of these nematodes have a wide host range and their dispersal has been favored by planting infested seedlings. This chapter discusses the main aspects of each of the plantain and banana PPN species and the non-conventional tools available for their adequate management. Although some chemical nematicides are efficient in controlling PPN associated with Musa spp. crops, they are being withdrawn from the market for their hazardous to the environment and human health. Thus, the PPN management should consider non-chemical tactics, before and after sowing, including the use of PPN free seeds, the spraying of biocontrol agents, and the use of phytochemical compounds applied via biofumigation, green manures, plant essential oils and extracts, intercropping, cover crops, improved fallow and crops rotation.